Review of the book The Protestant Ethic and Spirit of Capitalism - kamichi miyashiro, Manuel (2020)
This review aims to demonstrate the validity of Weber's argument today. To this end, the aspects of the ethics of assightetic Protestantism that the author indicates as the cause of the development of capitalism have been analyzed, and demonstrates how this economic system remains in place due to the continuity of ethics in people. Second, criticism from economists Jeffrey Sachs and Ha-Joon Chang has been answered to Weber's thesis when they show how capitalism has developed faster in Catholic than Protestant countries.